Before Utopia : the making of Thomas More's mind - Dealy, Ross (Toronto ; Buffalo ; London : University of Toronto Press, 2020)
"This unique study considers the influences of Stoic critics on the evolution of Thomas More's thought. The author argues that More's engaement with Erasmus's work radicalized his understanding of Christianity and shaped the writing of Utopia."--
3 Stoic Corrections of Epicureans: Moral Absolutes -- 4 Stoic Utile Expanded -- 5 Stoic Justice Expanded -- 6 Corollaries -- Part VII: Utopian Warfare: A Unitary Two-Dimensional Mindset -- 1 Super Machiavellians? -- 2 "Utter Loathing of War" and Yet a Thoroughly Militarized State -- 3 Righteous Cunning, Stratagem, and Ferocity -- 4 Beyond Machiavelli, a Seamless Mindset: Embryonic Soldiers of Christ -- Part VIII: What Wiseman Hythloday Did Not Understand -- Conclusion -- Bibliography -- Index
Includes bibliographical references and index.
Print version record.
JSTOR
Keywords: More, Thomas, -- Saint, -- 1478-1535.; More, Thomas, -- Saint, -- 1478-1535 -- Knowledge and learning; More, Thomas, -- Saint, -- 1478-1535 -- Religion; More, Thomas, -- Saint, -- 1478-1535 -- Sources; More, Thomas, -- Saint, -- 1478-1535.; More, Thomas, -- Saint, -- 1478-1535; Utopia (More, Thomas, Saint); LITERARY CRITICISM -- Renaissance; Learning and scholarship; Religion; Christianity; Cicero; Desiderius Erasmus; Enchiridion; Lucian; Renaissance; Seneca; Stoicism; The Praise of Folly; Thomas More; Utopia; historyof literature; intellectual history; philosophy; theology; Sources